PENINGKATAN KEMAMPUAN KOMUNIKASI MATEMATIS: DAMPAK PENDEKATAN MATEMATIKA REALISTIK INDONESIA (PMRI) BERNUANSA ISLAMI - Renny Saputri Yuliyanti; Ruhban Masykur; Indah Resti Ayuni Suri (Journal of Mathematics Education and Science, 2021)
The low ability of mathematical communication at SMP Negeri 1 Way Bungur, East Lampung is due to various factors, including the assumption that mathematics is complicated, a lack of curiosity about mathematics, and a lack of variation in learning models, so that students still tend to be passive. The purpose of this study was to determine the mathematical communication skills of students who use the Islamic-nuanced Indonesian Realistic Mathematics Education (PMRI) approach better than ordinary learning. The research method used is a quantitative method using the Quasi-Experimental Design method. The data collection techniques used in the study were: documentation, tests in the form of essay questions to determine the effect of the Islamic-nuanced Indonesian Realistic Mathematics Education (PMRI) approach to improve mathematical communication skills. This study indicates an increase in the mathematical communication skills of students who are given an Islamic approach to Indonesian Realistic Mathematics Education (PMRI) with ordinary learning. Increasing students' mathematical communication skills with the Islamic-nuanced Indonesian Realistic Mathematics Education (PMRI) approach is better than regular learning. So it can be concluded that the Islamic-nuanced Indonesian Realistic Mathematics Education (PMRI) approach can improve mathematical communication skills compared to ordinary learning. Abstrak Berdasarkan latar belakang dan rumusan masalah di atas, maka peneliti memiliki tujuan yaitu untuk mengetahui Pengaruh Pendekatan Pendidikan Matematika Realistik Indonesia (PMRI) bernuansa Islami dalam meningkatkan kemampuan komunikasi matematis yang terdapat pada peserta didik di SMP Negeri 1 Way Bungur. Metode penelitian yang digunakan adalah metode kuantitatif menggunakan metode Quasi Eksperimen Design.  Teknik pengumpulan data yang digunakan pada penelitian, yaitu: Dokumentasi, Tes berbentuk soal uraian (essay)  untuk mengetahui pengaruh pendekatan Pendidikan Matematika Realistik Indonesia (PMRI) bernuansa Islami untuk meningkatkan kemampuan komunikasi matematis. Hasil penelitian ini bahwa adanya pengaruh peningkatan kemampuan komunikasi matematis peserta didik yang diberi pendekatan Pendidikan Matematika Realistik Indonesia (PMRI) bernuansa Islami dengan pembelajaran biasa. Peningkatan kemampuan komunikasi matematis peserta didik dengan pendekatan Pendidikan Matematika Realistik Indonesia (PMRI) bernuansa Islami lebih baik daripada pembelajaran biasa. Sehingga dapat disimpulkan bahwa pendekatan Pendidikan Matematika Realistik Indonesia (PMRI) bernuansa Islami dapat meningkatkan kemampuan komunikasi matematis dibandingkan dengan pembelajaran biasa.